Enhanced cooperation and European tax law - Heber, Caroline, 1988- (Oxford : Oxford University Press, 2021)
The enhanced cooperation mechanism allows at least nine Member States to introduce secondary EU law which is only binding among these Member States. From an internal market perspective, enhanced cooperation laws are unique as they lie somewhere between unilateral Member State laws and uniform European Union law. The law creates harmonisation and coordination between the participating Member States, but may introduce trade obstacles in relation to non-participating Member States. This book reveals that the enhanced cooperation mechanism allows Member States to protect their harmonised values and coordination endeavours against market efficiency.
This edition also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on July 9, 2021).
Keywords: Taxation -- Law and legislation -- European Union countries